Financial integration and economic growth in Africa - Blanche, NGO Yonga Debra; Fidoline, NGO NONGA (Asian Journal of Empirical Research, 2024)
The main objective of this article is to assess the link between financial integration and economic growth in African countries during the period 1990-2017. To achieve this goal, we used a dynamic panel model using the generalized method of moments (GMM) in first difference with threshold effects on a sample of 29 African countries. The results of the estimates reveal, on the one hand, that the countries that benefit from the benefits of financial integration on economic growth are those with high trade and financial openness, high human capital, low inflation, democratic regime, and high public expenditure. On the other hand, these results indicate that financial integration is associated with a low probability of surviving a banking crisis in the countries studied. Thus, the governments of African countries must implement policies aimed at a progressive liberalization of trade and financial activities, coupled with the implementation of macroeconomic stability policies and the improvement of the quality of the institutional environment, which determines the impact of financial integration on economic growth.